Kajian Terhadap Pendekatan Pembelajaran Pelajar - Ismail , Maznah; Yoong, Suan (Penerbit Universiti Sains Malaysia, 1995)
The paper explores the learning approaches of Malaysian secondary school students. In addition, it attempts to examine the relationships between learning approaches, self-concept, locus of control and academic achievement. Malaysian versions of Learning Process Questionnaire (LPQ) which measures students' approaches to learning and Marsh's Self-Descriptive Questionnaire (SDQ) which measures various aspects of self-concept were administered to 53J Form Four students from five national secondary schools.